Strategi Dakwah Islam dalam Pendekatan Rasional Transendental - Andy Dermawan (Al-Jami'ah: Journal of Islamic Studies, 2002)
This article tries to apply the transcendental rational approach to the preaching of Islam. The characteristic preaching of Islam in transcendental rational approach relies on how ratio works in catching reality in the real world empirically, and then we analyze through an intergalactic combination between "fikir" and "zikir" to answer mankind's problems based on Allah's sayings and the prophet's tradition. The author tries to offer preaching of Islam's comprehension scientifically as follow: (1). Normatif preaching i.e., preaching of Islam which is based on Al-Qur'an and Hadith and is analyzed hermeneutical, dialectical, systematically in order to seize the moral teachings integrally without doing any reductions on both sources; (2). Historic preaching i.e., preaching of Islam which develops post Rasulullah's life up to recent days which is made as consideration to understand both sources (Al-Qur'an and Hadith). Whereas the characteristic of historic preaching is always open for changes, criticism, and giving reinterpretation and comprehension toward the reality of existing preaching.